The wandering astronomer - Moore, Patrick (Institute of Physics Pub., 1999)
Drawing on the author's knowledge and direct experience of the key events in astronomy and space exploration, this book takes a sideways look at the historical reports and contemporary thought behind a range of astronomical topics. It includes a collection of essays that cover various things from the case of vanishing planets to UFOs over Selsey.